2018
DOI: 10.1101/305300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Possibilities for improvement of humoral innate immunity in turkeys and hens in conditions of thermal stress by the immunomodulator Immunobeta

Abstract: SummaryThe experiments for evaluation of the effect of Immunobeta were performed with turkeys and organically reared layer hens. Turkeys received Immunobeta at a dose of 4 g/kg feed during the beginning of lay (cold period), thermoneutral period and hot summer period. In hens, two dietary levels of Immunobeta were tested: 2 g/kg and 4 g/kg. Blood serum and egg lysozyme levels, alternative pathway of complement activation (APCA) and beta-lysins concentrations were determined. It was found out that Immunobeta ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…In a similar experiment, Bozakova et al (2020) explored the possibilities for improvement of humoral immunity via the application of Immunobeta® immunomodulator among turkeys and hens.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar experiment, Bozakova et al (2020) explored the possibilities for improvement of humoral immunity via the application of Immunobeta® immunomodulator among turkeys and hens.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have shown that lysozyme is able to improve immunoglobulin A secretion and activate macrophage with a rapid riddance of bacterial diseases (Wang et al, 2005;Clarke et al, 2010;Dang et al, 2022). Thus, lysozyme is a natural antimicrobial protein considered a necessary component of innate immunity (Liu et al, 2010;Bozakova et al, 2020;Bastamy et al, 2024). According to these data, antibiotics can be replaced by lysozymes in the diet of poultry.…”
Section: Introductionmentioning
confidence: 99%